SAFETY STUDY OF ROMIPLOSTIM BIOSIMILAR - A. N. Afanasyeva; V. B. Saparova; D. D. Karal-Ogly; E. I. Mukhametzyanova; D. V. Kurkin; A. V. Kalatanova; I. E. Makarenko; A. L. Khokhlov; I. A. Lugovik (Фармация и фармакология (Пятигорск))
Idiopathic thrombocytopenic purpura is a chronic autoimmune hematological disease caused by an increased destruction of platelets and associated thrombocytopenia, for the treatment of which the imported drug romiplostim is used. Сreation of the drug biosimilar provides a reduction in the cost of therapy and an access for the treatment to more patients.The aim of the study was to compare the safety indicators of the reference drug and its biosimilar in vivo and in vitro.Materials and methods. In the in vitro study, a model of “complement-dependent cytotoxicity” induced by the complement was formed on the 32D hTPOR clone 63-cell line, followed by a cell viability measurement with the CellTitter Glo® kit. An in vivo part of the study was carried out on Javanese macaque monkeys (Macaca fascicularis). During the experiment, the clinical condition, mortality, appetite of the animals, their body weight, body temperature, respiratory rate were assessed, the clinical parameters of blood and urine of the animals were also monitored, and the hemostasis indicators were additionally measured.Results. In the in vitro experiment, the original drug romiplostim and its biosimilar GP40141 were compared in terms of EC50 values. The indicatirs did not show complement-dependent cytotoxicity. According to the in vivo results, no deviations were recorded in the clinical status of the animals and their feed intake, and no lethality was fixed out in the groups either. For all the parameters studied (body weight and temperature, respiratory rate, clinical urinalysis, clinical and biochemical blood tests, coagulation hemostasis), GP40141 and romiplostim, when administered at the doses equivalent to 10 toxic doses (TDs), had comparable effects.Conclusion. In the comparison of safety performance both in vitro and in vivo, the original drug romiplostim and its biosimilar GP40141 showed similar results.